The Effect of Internal Auditor Independence and Internal Control Systems on Fraud Prevention, with Institutional Environment as a Moderating Variable: A Study of Internal Auditors at the Buol Regency Inspectorate - Yuningsi Yuningsi; Haryono Pasang Kamase; Rudy Usman; Rahma Masdar (SAINTIS Publishing, 2026)
This study aims to analyze the effect of internal auditor independence and internal control systems on fraud prevention with institutional environment as a moderating variable. This study uses a quantitative approach with an explanatory research design. Data were obtained from internal auditors of the Buol Regency Inspectorate through an online questionnaire using Google Forms. The sampling technique used was census sampling. Data analysis was performed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method using SmartPLS software, which included testing the measurement model, structural model, and significance testing through the bootstrapping procedure. The results showed that the independence of internal auditors and internal control systems had a positive and significant effect on fraud prevention. However, the institutional environment was not proven to moderate the effect of internal auditor independence on fraud prevention, and was proven to negatively moderate the relationship between internal control systems and fraud prevention. These findings indicate that the effectiveness of internal audit and internal control systems in preventing fraud does not only depend on technical aspects, but is also greatly influenced by institutional environmental conditions. Therefore, strengthening a culture of integrity and institutional governance is important to improve the effectiveness of fraud prevention in the public sector.